Aspects of Content, Context and Adaptation Modeling in Mobile Learning Application Design - Bhaskar, Nagella Uday; Raju, Surya Narayana; Paladugu, Govindarajulu; Reddy, VenkataRamana (International Journal of Interactive Mobile Technologies (iJIM), 2013)
Mobile leaning application development has been influenced by the e-learning models, methods and a variation of these for the better understanding and accommodation of additional elements that prop up in m-learning scenarios and applications. Here uniquely designed models for various aspects of m-learning scenarios and situations by concentrating on Learner Styles or Contextual Features or Learning Content or Learner Behavior or Adaptation methods are proposed.